Spontaneous CNS remyelination in beta 2 microglobulin-deficient mice following virus-induced demyelination - Miller, DJ (J Neurosci, 1995)
Animal models with selective genetic immunodeficiencies are useful tools to identify pathogenic mechanisms of disease. Resistant (C57BL/6F 129/J) (H-2b) mice are rendered susceptible to Theiler's murine encephalomyelitis virus-induced demyelination by genetic disruption of the beta 2 microglobulin gene [beta 2 m(-l-)]. The absence of beta 2 m prevents the expression of major histocompatibility complex class I molecules and normal levels of functional CD8+ T cells. We tested whether genetic depletion of beta 2 m would permit CNS remyelination after chronic demyelination induced by the Daniel's strain of Theiler's virus. In contrast to the minimal spontaneous remyelination observed in SJL/J mice after infection with the Daniel's strain of Theiler's virus, chronically infected beta 2 m(-I-) mice showed extensive and progressive spontaneous CNS remyelination at 6, 12, and 18 months after infection. Spontaneous remyelination by both oligodendrocytes and Schwann cells occurred despite the presence of persistent virus antigen and RNA, but was associated with diminished virus-specific humoral and delayed-type hypersensitivity responses. These experiments support the hypothesis that the immune response inhibits myelin regeneration after virus-induced CNS demyelination.